2015
DOI: 10.1007/s40865-015-0017-y
|View full text |Cite
|
Sign up to set email alerts
|

Within-Individual Change in Arrests in a Sample of Serious Offenders: The Role of Identity

Abstract: Objective Paternoster and Bushway (2009) have recently proposed and developed Paternoster 2012, 2013) an identity theory of desistance (ITD). The current study is an initial attempt to empirically examine the tenability of the ITD by assessing whether self-identity and intentional self-change are critically involved in the desistance process among a sample of serious drug-involved adult criminal offenders. Methods Using arrest data from a sample of released prison inmates with non-trivial drug problems and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 56 publications
(100 reference statements)
2
24
0
Order By: Relevance
“…This finding mirrors the self-identity literature which posits that those who view themselves as prosocial are less likely to engage in antisocial behaviors than those who view themselves as deviant (Akerlof and Kranton 2010;Brownfield and Thompson 2005;Burke 1980;Burke and Stets 2011;Foote 1951). Nonetheless, this study adds to the desistance literature by expanding the scope of self-identity theories to account for the process of within-individual changes in misbehavior not just among adult offenders (e.g., Na et al 2015;Rocque, Posick, and Paternoster 2016) but also among the general youth population who did engage in violent behavior and are at risk of desistance. In model 3, we added some important time-varying covariates and time-stable characteristics to further minimize the selection bias that might yield an overestimated coefficient for the true relationship between prosocial identity and violence.…”
Section: Resultssupporting
confidence: 76%
“…This finding mirrors the self-identity literature which posits that those who view themselves as prosocial are less likely to engage in antisocial behaviors than those who view themselves as deviant (Akerlof and Kranton 2010;Brownfield and Thompson 2005;Burke 1980;Burke and Stets 2011;Foote 1951). Nonetheless, this study adds to the desistance literature by expanding the scope of self-identity theories to account for the process of within-individual changes in misbehavior not just among adult offenders (e.g., Na et al 2015;Rocque, Posick, and Paternoster 2016) but also among the general youth population who did engage in violent behavior and are at risk of desistance. In model 3, we added some important time-varying covariates and time-stable characteristics to further minimize the selection bias that might yield an overestimated coefficient for the true relationship between prosocial identity and violence.…”
Section: Resultssupporting
confidence: 76%
“…Using longitudinal data (the Rutgers Health and Human Development Project) and growth-curve models, Rocque, Posick, and Paternoster (2014) found that even net of a cluster of control variables, a favorable improvement in one's identity over time was related to a decline in offending. Most recently, Na, Paternoster, and Bachman (2015) using the same longitudinal data as the present study have estimated a growth-curve model, and found that offenders released from prison who became more favorable in their self-image over time and who took concrete steps to get help with their drug problem showed signs of moving toward desistance as reflected in period-to-period changes in both arrest and self-reported drug use. While there has yet to be a definitive quantitative study of identity change over time and desistance from crime, these few empirical efforts seem to indicate that one's identity is an important component of the desistance process.…”
Section: Empirical Findings On Identity and Desistancementioning
confidence: 61%
“…However, others have offered evidence that it is possible to disengage from offending without the internalisation of a non-offender identity (Nugent and Schinkel, 2016), and that persisters may continue offending despite a positive, prosocial identity and conformist values (Bottoms and Shapland, 2011;Liem and Richardson, 2014). A few longitudinal studies have found empirical support for the idea that a prosocial identity is associated with a decreased likelihood of future offending (Bachman, Kerrison, Paternoster, O'Connell and Smith, 2016;Bottoms and Shapland, 2011;LeBel et al, 2008;Na, Paternoster and Bachman, 2015;Rocque, Posick and Paternoster, 2016;Walters, 2018). What distinguishes successful desisters from persisters may be related to confidence in their ability to go straight and commitment to desistance, or a sense of agency (Burnett, 2013;Liem and Richardson, 2014; see also Farrall, 2002).…”
Section: Identity and Desistancementioning
confidence: 99%
“…Qualitative studies tend to approach identity inductively (what emerges from participants’ narratives) and holistically in relation to how participants see themselves, including goals, values, self-worth and roles. Quantitative studies deductively operationalise identity and tend to focus on one element, such as a sense of self-worth (Na et al, 2015) or the extent to which participants see themselves as prosocial (Bachman et al, 2016).…”
Section: Identity and Desistancementioning
confidence: 99%